Hepatic fibrosis in morbidly obese patients: fibroscan accuracy - Maged Tharwat Elghannam; Moataz Hassan Hassanien; Ahmed Aly ELRay; Hoda Mohamed Abu-Taleb; Yosry Abdelrahman Ameen; Gamal Mohammed ELattar; Emad Abdelwahab Turky; Mohammed Darwish ELTalkawy (Exploration of Digestive Diseases)
Metabolic associated steatotic liver disease (MASLD) stands as the most common hepatic disorder in both developed and developing countries. The global increasing rates in obesity rates are fuelling an increase in MASLD cases. Fibroscan, a transient elastography device, is a research-based, noninvasive method for assessing liver fibrosis. Accurately measuring the extent of fibrosis presents difficulties in a cohort of individuals who are severely obese with a body mass index (BMI) ≥ 40 kg/m2, particularly regarding the reliability and applicability of the XL probe. This study’s objective is to evaluate the precision of fibroscan in morbidly obese individuals with a BMI ≥ 40 kg/m2. We explored Google, PubMed, and Medline to gather information on fibroscan and its application for measuring fibrosis levels in morbidly obese patients ≥ 40 kg/m2 who have MASLD. The fibrosis levels obtained from the fibroscan do not consistently correlate with the clinical or histopathological data, which are essential for accurately determining liver stiffness measurement (LSM) cutoff values and/or ranges for these patients with either significant or advanced fibrosis. Additional prospective multicenter studies are necessary to better establish LSM cutoff values and/or ranges for patients suffering from significant or advanced fibrosis due to morbid obesity.